Analisis Kemampuan Keuangan Daerah Kabupaten Bone dalam Pengembalian Pinjaman Pemulihan Ekonomi Nasional - Arsyad, Andi Nurul Aulia; Nalien, Elvira Mulya (Research and Development Agency Ministry of Home Affairs, 2024)
Regional loans provide consequences for regions to make payments on the loan at the specified time. This article aims to find out how Bone Regency's financial capacity is to pay off PEN loans over the next eight years, analyzed using Debt Service Coverage Ratio (DSCR) by Mahmudi. DSCR consists of eight indicators, namely Regional Original Income, General Allocation Funds, Profit Sharing Funds, Reforestation Fund Profit Sharing Funds, Mandatory Expenditures, Loan Principal Installments, Loan Interest and Other Loan Costs. This article uses a qualitative approach using quantitative data. Data collection techniques include Semi-Structured Interviews, Passive Participant Observation and Documentation. The research results show that Bone Regency has the ability to repay PEN loans in the next 8 years and meets the minimum DSCR score criteria of 2.5 points. There are no obstacles in repaying PEN loans, but regional finances in 2024 are predicted to be burdened due to the implementation of regional elections. Efforts made to overcome obstacles to repaying PEN loans are by producing good financial reports. Also to anticipate a budget deficit that may occur in 2024, by budgeting a reserve fund that starts in 2022 and can be disbursed in 2024.